2010
DOI: 10.1007/s10126-010-9286-y
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Major Penaeid Shrimp EST Studies and the Construction of a Shrimp Transcriptome Database Based on the ESTs from Four Penaeid Shrimp

Abstract: By economic value, shrimp is currently the most important seafood commodity worldwide, and these animals are often the subject of scientific research in shrimp farming countries. High throughput methods, such as expressed sequence tags (ESTs), were originally developed to study human genomics, but they are now available for studying other important organisms, including shrimp. ESTs are short sequences generated by sequencing randomly selected cDNA clones from a cDNA library. This is currently the most efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 46 publications
5
37
0
Order By: Relevance
“…This result was confirmed in another transcriptome study from WSSV-challenged organisms (Leu et al 2011).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…This result was confirmed in another transcriptome study from WSSV-challenged organisms (Leu et al 2011).…”
Section: Introductionsupporting
confidence: 62%
“…The deduced amino acid sequence shares 72% and 77% identity with B. mori and H. sapiens, respectively. sNDK is overexpressed during WSSV infection (Clavero-Salas et al 2007;Leu et al 2011), but its biochemical activity has not been demonstrated yet.…”
Section: Introductionmentioning
confidence: 98%
“…Such progress included the development of molecular markers (Leu et al, 2011;Duan et al, 2013), generation of large-insert BAC libraries , construction of genetic and physical maps, and efforts for sequencing the entire genome of the penaeid shrimp (Shen et al, 2007;Du et al, 2010;You et al, 2010;Lin et al, 2012). These genomic resources made it possible to address the issues of disease resistance at the genome and transcriptome levels using various approaches such as microarrays (Zeng and Lu, 2009;Aoki et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…EST databases are rich resources for gene expression analysis, and can provide an informative overview of major transcripts in specific tissues. Many tissue-specific genes and expression profiles have been successfully characterized, which are highly useful in understanding the gene functions, tissue physiology and transcriptomics [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The cDNA library construction and expressed sequence tags (ESTs) analysis are efficient approaches to collect genomic information and identify useful genes [1,2]. They were developed originally to discover new human genes [1], but now are extensively used for studying genomics of important aquaculture animals including fishes [3,4], shrimps [5,6] and crabs [7,8].…”
Section: Introductionmentioning
confidence: 99%